The impact of higher education on female labor force participation in Saudi Arabia - Abdelatti, Hillo; Elhadary, Yasin; Ahmed, Abdalla (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this paper is to explore the impact of higher education on female participation in the labor force in Saudi Arabia. Specifically, it aims to statistically examine the relationship between the number of female graduates and their rate of participation in the labor force, as well as to uncover the role of GDP in this relationship. To achieve these objectives, official data from the Saudi Authority for Statistics were used, covering a 17-year period (2006-2022), along with several recently published relevant documents. Statistically, the paper employs both a regression model and an independent samples t-test to analyze the relationship. The findings confirm a strong positive correlation between the number of female graduates and their participation in the labor force, with a correlation coefficient (R) of 0.993, and a coefficient of determination (R-square) of 0.986. Despite this encouraging result, gender disparity in employment remains. Although the number of female graduates has substantially surpassed that of males, their participation in employment is still significantly lower. Key recommendations include addressing socio-cultural barriers that limit females' full participation in the workforce. This paper contributes to the current debates on the relationship between higher education, GDP, and female labor force participation in Saudi Arabia.